Problematika Pembatalan Hak Pengelolaan Milik PT. Inalum (Persero) atas Gugatan Cacat Prosedural dan Bertentangan dengan Asas Umum Pemerintahan yang Baik (Studi Putusan Nomor 43/G/2022/PTUN-MDN) - Simanjuntak, Agnes Vepy; Lubis, Muhammad Yamin; Sembiring, Rosnidar; Zaidar, Zaidar (Journal of Law & Policy Review, 2023)
Problems in the issuance of Management Rights Certificates are land problems that commonly occur in Indonesia as well as the resistance carried out by Tekardjo Angkasa against PT. Inalum (Persero). The problem studied is the existence of PT. Inalum (Persero) as the owner of Management Rights, legal certainty over civil ownership rights based on the basis of land certificate rights owned by Tekardjo Angkasa and legal considerations by the panel of judges in case Number 43/G/2022/Ptun-Mdn. The research method used is normative legal research which is presented descriptively. The research approach is carried out through the case approach method and the statutory approach. Data sources are obtained from primary, tertiary and secondary legal sources. Data is processed qualitatively and deductively inferred. The result of this research is the existence of PT. Inalum (Persero) obtained from state land in the form of contradictory decisions. SKT mer ownership